2005
DOI: 10.1111/j.1442-1984.2005.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Miyamasukashi‐yuri (Lilium maculatum Thunb. var. bukosanense), an endemic and endangered species at Mount Buko, Saitama, Japan

Abstract: Lilium maculatum var. bukosanense, Miyamasukashi-yuri in Japanese, grows endemically in Saitama Prefecture, Japan, and is listed in the Saitama Prefecture Red Data Book as a critically endangered plant. Articles about its genetic diversity and population genetic structure have not been reported. Before it is lost, population genetic studies can provide information for efficient in situ conservation as well as for possible future use in breeding programs. Therefore, we carried out a population genetic study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
(56 reference statements)
2
17
0
Order By: Relevance
“…The percentage of polymorphic fragments varied from 66.6 to 100%, with an average of 87.5% (Table 4). These results are similar with those reported by Yamagishi et al (2002) and Arzate-Fernández et al (2005b), who used these ASSR primers and proved their efficiency for detecting high polymorphism percentage in different species of the genus Lilium.…”
Section: Issr Markerssupporting
confidence: 82%
See 1 more Smart Citation
“…The percentage of polymorphic fragments varied from 66.6 to 100%, with an average of 87.5% (Table 4). These results are similar with those reported by Yamagishi et al (2002) and Arzate-Fernández et al (2005b), who used these ASSR primers and proved their efficiency for detecting high polymorphism percentage in different species of the genus Lilium.…”
Section: Issr Markerssupporting
confidence: 82%
“…In each primer, the anchor consisted of a triplicate of distinct sequence (Table 4). The amplification conditions for the primers 3'-ASSR02 and 3' -ASSR15 were those described by Arzate-Fernández et al (2005b), and consisted of an initial cycle of 9 min at 94 °C, 1 min at 46 °C and 1 min at 72 °C and a final cycle of 9 min at 94 °C, 1 min at 46 °C and 10 min at 72 °C. For primers 3'-ASSR20, 3'-ASSR29 and 3'-ASSR35, the amplification cycles were those used by Yamagishi et al (2002) and consisted of an initial cycle of 9 min at 94 °C, 1 min at 46 °C and 1 min at 72 °C and a final cycle of 10 min at 72 °C.…”
Section: Issr Markersmentioning
confidence: 99%
“…This suggests that the ISSR markers can be a highly informative, fast, and reliable system for the genetic diversity studies as reported by Liu et al (2011). Our results also suggest that the CT sequences may be very abundant in the genomes of wild ornamental species because the primers that were used here have been also useful for determining the genetic diversity of other ornamental wild species such as Lilium maculatum (Arzate-Fernández et al, 2005), Tigridia pavonia (Piña-Escutia et al, 2010a), and Sprekelia formosissima (Bautista-Puga et al, 2011).…”
Section: Issr Markerssupporting
confidence: 58%
“…The mean of total and the polymorphic fragments that were generated per primer were 6.4 and 4.2, respectively. ISSR markers have been successfully used to estimate the extent of genetic diversity in a wide range of crop and wild species, including lily (Arzate-Fernández et al, 2005), jacaranda (Escandón et al, 2005), citronella (Bhattacharya et al, 2010), and ginseng (Li et al, 2011). The ISSR marker efficiency has been attributed to motif sequences, as well as the sequence of its anchor.…”
Section: Issr Markersmentioning
confidence: 99%
See 1 more Smart Citation